2018
DOI: 10.6061/clinics/2018/e450s
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency in ovarian cancer: a review of its epidemiology and management

Abstract: Ovarian cancer patients with homologous recombination deficiencies exhibit specific clinical behaviors, and improved responses to treatments, such as platinum-based chemotherapy and poly (ADP-ribose) polymerase (PARP) inhibitors, have been observed. Germline mutations in the BRCA 1/2 genes are the most well-known mechanisms of homologous recombination deficiency. However, other mechanisms, such as germline and somatic mutations in other homologous recombination genes and epigenetic modifications, have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…Interestingly, the study by Ren JG et al found that citrate suppressed tumor growth through inhibition of glycolysis, the TCA cycle and the insulin-like growth factor-1 receptor pathway (Ren et al, 2017). Homologous recombination deficiency was closely related to ovarian cancer and breast cancer (Zhao et al, 2017; Da et al, 2018). These examples show that the results of GESA analysis can be used as a reference for oncogenesis studies to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study by Ren JG et al found that citrate suppressed tumor growth through inhibition of glycolysis, the TCA cycle and the insulin-like growth factor-1 receptor pathway (Ren et al, 2017). Homologous recombination deficiency was closely related to ovarian cancer and breast cancer (Zhao et al, 2017; Da et al, 2018). These examples show that the results of GESA analysis can be used as a reference for oncogenesis studies to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Double-strand DNA breaks are repaired by homologous recombination (HR). The germline BRCA1/2 genes are involved in HR mechanism and their mutation may lead to HR deficiency (HRD) [ 95 ]. HRD alone does not always induce apoptosis as other repair mechanisms can prohibit accumulation of damaged DNA.…”
Section: Future Io Treatment Strategiesmentioning
confidence: 99%
“…HRD alone does not always induce apoptosis as other repair mechanisms can prohibit accumulation of damaged DNA. However, impairing two DDR mechanisms by adding PARPi to HR-deficient cells can lead to cell death (synthetic lethality) [ 95 ].…”
Section: Future Io Treatment Strategiesmentioning
confidence: 99%
“…Nine per cent of ovarian cancers have a somatic (non-inherited, tumour-specific) BRCA mutation, and 18% have other HRD mutations, which makes both groups respond to molecular targeted therapies that inhibit the enzyme PARP. 24 Accordingly, PARPis are particularly active in gBRCA mutation carriers and also show activity in women with somatic BRCA (sBRCA) mutations and HRDs, but at a lower rate. Olaparib is one PARPi that, when used as oral maintenance treatment in gBRCA mutation carriers, has shown 60% DFS at three years, compared with 27% in controls.…”
Section: Adjuvant Treatmentmentioning
confidence: 99%